Social determinants of labor market status of ethnic minorities in Britain - Martin Kahanec; Mariapia Mendola (Institute for the Study of Labor (IZA), 2007)
The labor market outcomes of ethnic minorities in advanced societies and their dependence on social relationships and membership in social networks are important empirical issues with significant policy consequences. We use detailed micro-data on multiple-origin ethnic minorities in England and Wales and a discrete choice model to investigate these issues. We find that the core family structure and contacts with parents and children away (in Britain) increases the probability of self-employment. On the other hand, engagement in organizational social networks is more likely to channel the same people into paid employment. Finally, disaggregating different types of social networks along their compositional characteristics, we find that having ethnic friends is positively associated with the likelihood to be self-employed while integration in mixed or non-ethnic social networks facilitates paid employment among minority individuals. These findings hint at a positive role of social integration on employment opportunities of ethnic communities in host societies.
Keywords: 330; Labor market; self-employment; ethnic minorities; social ties; Ethnische Gruppe; Erwerbstätigkeit; Selbstständige; Ausländische Arbeitskräfte; Familiensoziologie; Soziales Netzwerk; Großbritannien